PENYULUHAN KEPADA MASYARAKAT TERKAIT PENYEBAB TERJADINYA GASTRITIS - Dessy Adelia Pramesty; Doni Iswandani (Jurnal Pengabdian IKIFA, 2024)
The level of awareness among Indonesian people regarding gastric health is still low, with diseases related to gastric health being among the 10 most common outpatient diseases at the DKI Jakarta Provincial Health Center. One of the frequent causes of gastritis is a poor diet. Sufficient knowledge about gastritis is essential for each individual because if left untreated, it can damage stomach function and increase the risk of developing cancer. This is the background to the Community Service (PkM) activities of the IKIFA STIKes lecturer team. The PkM activities were conducted on 26 February 2024 in the Duren Sawit Subdistrict area to educate about the cause of gastritis. The targets for PkM activities are residents from several RW areas in Duren Sawit Village, totaling 34 respondents. During the PkM activities, respondents actively participated in discussing the topics presented. Therefore, it can be concluded that this PkM activity was successful based on the objectives set at the beginning.